Household Mobility in America : Patterns, Processes, and Outcomes - Gillespie, Brian Joseph (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book provides an interdisciplinary analysis of the correlates and consequences of residential relocation. Drawing on multiple nationally representative data sets, the book explores historic patterns and current trends in household mobility; individuals' mobility-related decisions; and the individual, family, and community outcomes associated with moving. These sections inform later discussions of mobility-related policy, practice, and directions for future research. .